INNOVATIVE OBSOLESCENCE IN MECHANICAL ENGINEERING AND SINGLENESS OF INDICATORS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The purpose of the present work is to present the manifestation of innovative obsolescence in mechanical engineering and the unequivocalness of the indicators - service life, reliability, physical wear, innovative and programmed obsolescence. The innovation life cycle and when innovation obsolescence occurs are presented. It has been proven that innovation obsolescence is a regularity that manifests as a consequence of the occurring change in the technical levels of innovations with the same technical purpose. The development is based on the thesis that between innovation development and innovation obsolescence there are certain interrelationships and interdependencies that essentially characterize the process of innovation obsolescence itself. In subsequent publications, an analysis of the dependencies and factors influencing the innovation process in the industry will be presented, regarding: constructive solutions, materials, processing processes, costs, demand and supply, price and obsolescence of solutions.